Bagaimana meningkatkan school well-being? Memahami peran school connectedness pada siswa SMA - Ulifa Rahma; Faizah Faizah; Yuliezar Perwira Dara; Najwa Wafiyyah (Jurnal Ilmiah Psikologi Terapan, 2020)
Objectives: this research was conducted to look at the relationship between school and school - both in high school students.Method: this research is a quantitative study involving subjects consisting of 134 high school students based on the calculation of the application G * Power version 3.1.9.2. Data retrieval is done by connecting two scales, namely the scale of school connectivity and school scale using the accidental sampling method. Test data analysis in this study using Pearson product moment.Findings: There was positive relationship between  school connectedness and school wellbeing variables in the Middle School students is significan (r = 0.77, p = 0.00) t. The results of this study have a positive value. Where there is a positive relationship between variables, the higher the level of student school connection to the school, the higher the school level will be, and vice versa.Conclusions: dimensions of school connectedness related to school wellbeing are related and liked by students, communication and liked by teachers. But belonging does not have an influence on school wellbeing in high school students. The dimension of school connectednes which has the greatest effect size is liked by the teachers then communication and the last is connected and liked by students.